Saline extraction as a method of obtaining a mixture of biologically active compounds of protein nature from a porcine pancreas - E. R. Vasilevskaya; M. A. Aryuzina; E. S. Vetrova (Пищевые системы, 2021)
A relevant solution to the problem of processing meat industry waste in Russia is to obtain useful biologically active compounds from abundant organs. The aim of this study was to examine the effectiveness of the saline extraction as a method for extracting a mixture of promising biologically active compounds from the porcine pancreas, as well as to determine the optimal time for the process. The study consisted of extraction of the porcine pancreas with 0,9% sodium chloride solution for 5 h 30 min with further determination of the total protein concentration and proteomic profile of the samples taken throughout the process. Based on the analysis of the dependence of the total protein content in the extractant on time, the optimal extraction time was determined to be 135–150 minutes. When studying the results of electrophoresis and the data of their processing, the optimal extraction time for the targeted isolation of the low-molecular fraction of compounds was also determined to be 90 min. At the same time, 13 protein bands with a molecular weight of 52 kDa and below were found on the electropherograms. Saline should be considered applicable for obtaining extracts rich in biologically active substances, incl. hormones, enzymes and other physiologically active compounds.